Online Alternative Dispute Resolution for Consumer Dispute Settlement in the Digital World - Ahmad Habib Al Fikry; Nurul Fibrianti (Universitas Muhammadiyah Tangerang, 2022)
Online dispute resolution by consumer dispute resolution agency has not been regulated in consumer protection law. The aims of this study: (i) showing online alternative dispute resolution is concept of consumer dispute resolution by consumer dispute resolution agency in digital world in Indonesia; (ii) showing the urgency of regulation and matters regulated in consumer protection law relating to online alternative dispute resolution. The author uses normative juridical research. The results show first, online alternative dispute resolution for consumer dispute resolution by consumer dispute resolution agency can overcome the problem of long time and not cheap costs incurred by consumers to resolve disputes, in line with the increase in digital consumers, whose implementation can improve assessment of alternative dispute resolution related to effectiveness rule of law. Second, online alternative dispute resolution needs to be regulated in consumer protection law so that consumer dispute resolution agency get legal certainty to apply them in consumer dispute resolution. Regarding the regulation, it can refer to International Council for Online Dispute Resolution and strengthen the institution of consumer dispute resolution agency. The regulation and implementation of online alternative dispute resolution by the consumer dispute resolution agency has been strengthened by success in several other countries.